2003
DOI: 10.1161/01.cir.0000056766.45109.c1
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Stimulated Cyclic Guanosine Monophosphate Inhibits Vascular Smooth Muscle Cell Migration by Inhibiting Ca/Calmodulin-Dependent Protein Kinase II

Abstract: Background-Insulin resistance is associated with vascular disease. Physiological concentrations of insulin inhibit cultured vascular smooth muscle cell (VSMC) migration in the presence of nitric oxide, and the failure to do so in insulin-resistant states may aggravate vascular disease. We sought to determine the molecular mechanisms by which insulin inhibits VSMC migration. Methods and Results-Insulin at 1 nmol/L stimulated cGMP production in cultured rat VSMCs that were induced to express inducible nitric oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 43 publications
(46 reference statements)
3
29
1
Order By: Relevance
“…Insulin has been shown to inhibit, to have no effect, and to stimulate cultured VSMC migration depending on the experimental conditions (9)(10)(11)(12)(13). The present study has demonstrated that insulin can induce a low level of migration in human coronary smooth muscle cells in two distinct assays.…”
Section: Discussionmentioning
confidence: 51%
“…Insulin has been shown to inhibit, to have no effect, and to stimulate cultured VSMC migration depending on the experimental conditions (9)(10)(11)(12)(13). The present study has demonstrated that insulin can induce a low level of migration in human coronary smooth muscle cells in two distinct assays.…”
Section: Discussionmentioning
confidence: 51%
“…Yet, the mechanisms underlying PKG-dependent increase in migration of immune cells are unknown. In smooth muscle and endothelial cells, PKG signaling has been reported to both stimulate and inhibit motility (Brown et al, 1999;Dubey et al, 1995;Kawasaki et al, 2003;Rolli-Derkinderen et al, 2010;Smolenski et al, 2000;Zhang et al, 2003); these conflicting results may be explained by differences in primary cell cultures and/or variations in cell migration assays. While the inhibitory effects are mediated, at least partly, through PKG phosphorylation of VASP or induction of MAP kinase phosphatase-1 (Jacob et al, 2002;Smolenski et al, 2000), pro-migratory effects of PKG depend on activation of phosphatidylinositol 3-kinase and RhoA phosphorylation (Kawasaki et al, 2003;Rolli-Derkinderen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, cGMP was recently proposed to be involved in other signaling pathways including MAPK1 20 and CaMKinase II cascade. 21 In addition, while recent analysis of the promoter region of murine Npr1 has revealed the presence of several binding sites for a variety of nuclear factors, including HFH-3, CREB, SRY, and USF, 14 no known transcription factors matched the cGMP-RE sequence, 15 suggesting that this is a novel cisacting element. Although the element described here was identified in the promoter regions of mouse, rat, and human Npr1, our search did not detect an identical element in the promoters of other cGMP-regulated genes, suggesting a specific mode of regulation for Npr1.…”
Section: Discussionmentioning
confidence: 99%